210k views
4 votes
2 m 3 − 14 m 2 + 20 m = 0

2 m 3 − 14 m 2 + 20 m = 0-example-1
User Baywet
by
5.9k points

1 Answer

3 votes

Given:


2m^3-14^(m2)+20m=0

Aim:

We need to find the values of m.

Step-by-step explanation:

Take out the common term 2m from the equation.


2m(m^2-7m+10)=0

Divide both sides by 2.


(2m)/(2)(m^2-7m+10)=(0)/(2)


m(m^(2-)7m+10)=0.
Use\text{ -7m=-5m-2m.}


m(m^2-5m-2m+10)=0.


m(m(m-5)-2(m-5))=0.


m(m-5)(m-2)=0.


m=0,(m-5)=0,(m-2)=0.


m=0,m=5,m=2.
m=0,2,5.

Final answer:


0,2,5.

User Valent Richie
by
5.8k points